Comparison of Operating Costs and LOS of Cesarean Section Patients Using ERACS and Non-ERACS Method - Puspitasari, Cinthya Dwi Cahyani; Paripurna, Yoga; Trianasari, Nurvita (Jurnal Jaminan Kesehatan Nasional, 2024)
The rate of births with cesarean section delivery in Indonesia is increasing. Along with the increasing rate, various clinical methods are used to reduce maternal morbidity and mortality, one of which is the Enhanced Recovery After Cesarean Section (ERACS). ERACS aims to speed up recovery, reduce postoperative complications, shorten length of stay (LOS) and lower patient care operational costs of cesarean section. The purpose of this study is to compare operational costs and LOS of cesarean section patients with ERACS and non-ERACS methods.The reseach used was case-control study which was carried out at RSUD dr. Rehatta Kelet from October-December 2022. This study involved 71 patients who met the inclusion criteria. Data were obtained from the patients’ medical records. The data were analyzed by mann Whitney Test using SPSS software. The result shows that the difference in LOS and operational costs using ERACS and non-ERACS was statistically significant at P=0.0001. The study concludes that ERACS method reduces LOS and operational costs compared to non-ERACS methods. The authors recommend that the association of obstetricians and gynaecologists should encourage its members to apply EARCS whenever possible.